Keterkaitan Laporan Keuangan Akuntansi Syari’ah dengan Laporan Keuangan Akuntansi Pajak - Rahmansyah Ritonga (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2016)
The financial statements Accounting shari'a when viewed in terms of the purpose is very different from the Tax Accounting, but in terms of meaning and integrity, financial statement accounting and tax accounting Shari'ah has some similarities, which are equally requires honesty presenters unconditionally. Accounting Shari'ah values are expected to purify worship (zakat, etc.) that are based on accounting profits Shari'ah. Similarly, Tax Accounting is expected to provide information on the number of taxable income, so that it can be calculated the amount of his tax liability. Accounting Shari'ah has inherent feature and non-negotiable that displays the ultimate truth (honest), and creates a sense of justice for all the users report. It is, of course becomes very interesting when associated with tax reporting embracing system of self-assessment, because the Self Assessment system, Taxpayer is given authority to calculate, calculate, deposit and report its own amount of tax payable.